Quadrant glitch analysis for ball screw driven positioning stage using friction compensation model feedforward - Nur Aidawaty , Rafan; Zamberi, Jamaludin; Tsung , Heng Chiew; Lokman , Abdullah; Mohd Nazmin , Maslan (2014)
This paper presents quadrant glitches analysis using various classical feedforward controllers for sliding and presliding regime. An aircut tracking in a circular motion is performed using an XY positioning stage with certain amplitude and velocities. Static friction model, Generalized Maxwell Slip (GMS) model and combination of both models are applied with feedforward Proportional-Integral-Derivative (PID) controller for this study. Radial error is obtained and tabulated according to the respective angle to show glitches at each quadrant. Motion reversal due to the sinusoidal input near zero velocity in a circular motion developed Stribeck effect. Due to stick-slip motion within a certain amplitude and frequency had generated glitches near zero positions. Comparing results of glitches produced with and without friction feedforward controller, reduction of errors has been observed. The glitches have a higher reduction in lower velocity. With a combination of static friction model and GMS model, the magnitude of quadrant glitches has better reduced and overall tracking errors, as well.